Consumer Cash Usage: A Cross-Country Comparison with Payment Diary Survey Data - John Bagnall; David Bounie; Kim P. Huynh; Anneke Kosse; Tobias Schmidt; Scott Schuh; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2014)
We measure consumers' use of cash by harmonizing payment diary surveys from seven countries. The seven diary surveys were conducted in 2009 (Canada), 2010 (Australia), 2011 (Austria, France, Germany and the Netherlands), and 2012 (the United States). Our paper finds cross-country differences – for example, the level of cash usage differs across countries. Cash has not disappeared as a payment instrument, especially for low-value transactions. We also find that the use of cash is strongly correlated with transaction size, demographics, and point-of-sale characteristics such as merchant card acceptance and venue.
Keywords: E41; D12; E58; 330; Money Demand; Payment Systems; Harmonization; Zahlungsverkehr; Geldnachfrage; Bargeld; Eurozone; USA; Kanada; Australien